Compatibility of Different Formulations in Pentravan® and Pentravan® Plus for Transdermal Drug Delivery - Hudson Polonini; Sarah Taylor; Clark Zander (MDPI AG, 2021)
The potential therapeutic benefit of transdermal delivery systems for some active pharmaceutical ingredients (APIs) has been well-established for decades within the scientific community. However, together with the clinical efficacy, there is the need for an evaluation of the stability of such APIs in bases with known transdermal capabilities, which is necessary to provide the compounding pharmacist with confidence when providing transdermal products. In this study, the stability of danazol, metformin HCl, and resveratrol as individual ingredients, as well as metformin HCl, resveratrol, and Vitamin D3 in combinations at bracketed high and low concentrations, were evaluated over a period of 6 months, using a ready-to-use transdermal vehicle for compounding pharmacies (Pentravan® or Pentravan® Plus). The five formulations tested (F1: Danazol 50 mg/g + MiodesinTM 85 mg/g in Pentravan®, F2: Metformin HCl 200 mg/g in Pentravan®, F3: Resveratrol 200 mg/g in Pentravan®, F4: Metformin HCl 100 mg/g + Resveratrol 100 mg/g + Vitamin D3 5000 IU in Pentravan®, and F5: Metformin HCl 200 mg/g + Resveratrol 200 mg/g + Vitamin D3 5000 IU in Pentravan® Plus) presented a beyond-use date of at least 6 months, presenting high convenience for the compounding pharmacies.